Cortical venous thrombosis in high altitude; result of an observational study - Pimpalwar, Yayati; Gurung, Brikshya; Sharma, Vyom (International Journal of Research in Medical Sciences, 2022)
Background: High altitude, an extremely rare cause of cortical venous thrombosis (CVT) has no literature review available signifying the relation between two as per date. The aim of this study is to establish the relation of exposure to high altitude and occurrence of CVT in properly acclimatised healthy individuals exposed to high altitude having no pre-existing morbidities. Methods: An observational type of prospective study was conducted at a tertiary care centre in North India. Patients who were sent back from a high-altitude area with CNS symptoms (headache to coma) were included in the study. Magnetic resonance imaging (MRI) and magnetic resonance venography (MRV), blood investigations including complete blood count and D-dimer were done as routine examinations in all these patients. MRI and MRV findings were recorded and analyzed for features of CVT. Results: Twenty-eight patients with an average age of 31.5 years (23-51 years) were included in the study. All patients had CNS symptoms; with headache being the common symptom. In the patients of CVT, there were MRI features of parenchymal infarct in 7 (25%), hemorrhagic infarct in 11 (41.6%), subarachnoid hemorrhage in 7 (25%) and mass effect in 3 (8.4%) patients. MRV revealed involvement of multiple sinus involvement more common than single sinus involvement, of which most commonly involved sinuses were Superior sagittal sinus and transverse sinuses. D-Dimer levels were significantly raised in 23 (83%) patients. Conclusions: High altitude though a rare cause, can be the single most important contributory factor in the development of CVT in healthy acclimatised individuals with no predisposing factors. The physicians dealing with such patients at high altitude should be well aware of the scenario as early diagnosis via imaging and prompt management can drastically reduce mortality in this potentially lethal but treatable conditions.